HUBUNGAN ANTARA TOXIC FRIENDSHIP DENGAN KESEHATAN MENTAL PADA REMAJA DI SURABAYA - Rika Amalia Kusnata; Agus Poerwanto; Fety Khosianah (Universitas Muhammadiyah Surabaya, 2025)
Abstract The purpose of the study below was to determine the correlation between toxic relationships in friendship and the mental health of adolescents in Surabaya. Using a quantitative correlational design, data were collected through a psychological scale given via Google Forms to 100 adolescents in Surabaya. The research data collection technique used in this study was the incidental sampling. Data collection in the study used a Likert scale arranged based on aspects of both variables. The results showed a significant negative correlation (r = -0). 309, p = 0.002) between mental health and toxic relationships, indicating that lower mental health increases the likelihood of involvement in toxic relationships. The results of this test suggested that when associated together, mental health and toxic relationships have a significant relationship (Sig.). The contribution of the mental health variable to toxic relationships is 0.309, which indicates that mental health has an influence of 30.9% on toxic relationships, while 69.1% is influenced by other factors. Therefore, the hypothesis in this study is accepted, which states that there is a significant correlation between mental health and toxic relationships in adolescents in Surabaya. Keywords: toxic relationship, mental health, teenagers